HRIS dan Kinerja Pegawai Perbankan: Employee Wellbeing sebagai Mekanisme Peningkatan Kinerja (Studi Bank X Makassar) - Endang Halimah; Isiswanty Isiswanty; Koas Diana; Andi Dewi Haryanti Agustang; Abu Said Uddin; Andi Firdania (Jurnal Teknologi dan Bisnis Cerdas, 2025)
Digital transformation in human resource management has become a strategic necessity for the banking industry to enhance employee effectiveness and performance. One of the key forms of this transformation is the implementation of a Human Resource Information System (HRIS), which integrates functions such as attendance, payroll, performance appraisal, self-service, and training. This study aims to examine the effect of HRIS implementation on employee performance, with employee wellbeing as a mediating variable, at Bank X in the Makassar area. A quantitative approach was employed using a survey method involving 150 employees of Bank X Makassar who actively use HRIS in their daily work activities. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that HRIS implementation has a positive effect on employee performance and employee wellbeing. Furthermore, employee wellbeing has a positive effect on employee performance and partially mediates the relationship between HRIS implementation and employee performance. These findings highlight that HRIS serves not only as an administrative tool but also as a strategic support system that enhances employee wellbeing and sustainable performance in the banking sector.